PENINGKATAN AKTIVITAS DAN HASIL BELAJAR SISWA DENGAN KOMBINASI MODEL PEMBELAJARAN KOOPERATIF JIGSAW DAN NUMBERED HEAD TOGETHER (NHT) PADA MATERI SISTEM EKSKRESI MANUSIA KELAS XI IPA 2 SMA NEGERI 5 MEDAN - Dewi Ratih; Erlintan Sinaga (Universitas Negeri Medan, 2017)
This study aims to improve the activity and results of Student Learning with the Combination Model Cooperative Jigsaw and Numbered Head Together (NHT) on Human Excretion system Material Class XI IPA 2 SMA Negeri 5 Terrain Learning Year 2015/2016. This type of research is action research (PTK) done in two cycles of study. The subjects were students of class XI IPA 2 totaling 40 people. At each cycle is held test learning outcomes in the form of multiple choice questions numbered 30. The results of this study showed that the average value of the pre-test students at the beginning of the learning process is 35.71, with classical learning completeness 0% (no value students who achieve KKM 70). The results of post-test student learning, indicating an increase, of student learning outcomes in the first cycle to the second cycle. The average post-test learning outcomes of students in the first cycle was 64.19, there are 22 students who completed reached KKM and value of classical completeness 55% (not yet complete because it has not reached the classical completeness criteria of ≥ 85%). The average results of students in the second cycle is 74.20, there are 34 students who completed reached KKM and value of classical completeness 85% (complete, since it has already reached the criteria of classical completeness of ≥ 85%). An increase in biology student learning outcomes by 30%. As a percentage of the activity of students in the first cycle and the second cycle, indicating an increase. In the first cycle of students' level of activity of 60% increased to 87.5% in the second cycle. An increase in biology student learning outcomes by 27.5%. Thus we concluded that the combination of Cooperative Model Jigsaw and Numbered Head Together (NHT) can improve biological activity and learning outcomes of students in class XI IPA 2 SMA Negeri 2 Medan in the academic year 2015/2016.Keywords: Learning Outcomes, Student Activities, Model Jigsaw, Numbered Head Together (NHT), cycle, Human Excretion system.